Calibration of urban canopies albedo and 3D shortwave radiative budget using remote-sensing data and the DART model. Issue 1 (1st January 2018) - Landier, L.; Gastellu-Etchegorry, J. P.; Al Bitar, A.; Chavanon, E.; Lauret, N.; Feigenwinter, C.; Mitraka, Z.; Chrysoulakis, N.
ABSTRACT: The derivation of the radiative budget of urban environments has gained a high interest in the recent years as an essential part of the global energy budget of big cities. Urban 3D (three-dimensional) heterogeneity hampers its assessment with in-situ measurements, which stresses the interest of Earth Observation (EO) satellites. Improvements in remote-sensing technology and 3D urban databases open the way to new deterministic approaches. This paper presents a new method that derives maps of urban shortwave exitance, albedo and radiative budget * from EO satellite images (e.g. Sentinel 2, Landsat-8), using the discrete anisotropic radiative transfer model. In a preliminary step, it derives maps of urban material optical properties from an EO satellite image, at the spatial resolution of this EO image. The method is applied to the city of Basel, Switzerland, in the frame of the European Community H2020 URBANFLUXES (www.urbanfluxes.eu ) project which aims at improving our knowledge on anthropogenic heat fluxes in European cities. Results are very encouraging. Indeed, urban * derived from 234 EO satellite images, ranging from 200 to 800 W/m 2 through the year, is very close to in-situ measured *: ≈15 W/m 2 temporal root mean square error (i.e. 2.7% mean relative difference) relative to measurements.